Holy war : cowboys, Indians, and 9/11s - Anderson, Mark Cronlund, 1960- (University of Regina Press, 2016)
"Noam Chomsky and George W. Bush seldom agree, but they both argued that 9/11 stood alone in American history. Although the use of airplanes as weapons of mass destruction was new, Mark Anderson maintains that the response to the attack was not: it was, in fact, as old as the Republic itself. Beginning with the Mexican-American War and ending with the invasion of Iraq, Holy War probes presidential speeches, news reports, editorial cartoons, television programs, and films to uncover how the United States reverts back to its creation mythology of "fighting Indians" to justify centuries of American imperialism."--